DETEKSI FRAUDULENT FINANCIAL REPORTING MENGGUNAKAN FRAUD PENTAGON - Runi Anjeli; Novianti, Neva; Rahmawati, Novia; Rifa, Dandes (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2024)
This study aims to provide empirical evidence on the effect of fraud pentagon in detecting fraudulent financial reporting empirical study on State-Owned Enterprises listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique used purposive sampling with a final sample of 21 companies. This study uses a panel data regression model with e-views 12. The results of the study show that financial targets have a significant positive effect on fraudulent financial reporting, while external pressure has a significant negative effect. Financial stability, institutional ownership, ineffective monitoring, auditor quality, and change in auditor do not show a significant effect. Changes in directors and frequent number of CEO's pictures also do not have a significant effect. Practically, companies are advised to focus on managing financial targets and external pressure to reduce the risk of inaccurate financial reporting. From an academic perspective, this study enriches the literature by highlighting the important role of financial targets and external pressure, and encouraging further research on other factors that influence fraudulent financial reporting. The results of this study are expected to deepen the understanding of fraudulent financial reporting predictions.